Orographic drag on islands in the NWP mountain grey zone. (9th October 2016) - Vosper, S. B.; Brown, A. R.; Webster, S.
Abstract : The drag due to resolved and subgrid flow blocking and gravity waves is examined in simulations of flow over mountainous islands at 'grey zone' resolutions, in which the processes are neither well resolved or fully subgrid‐scale. Simulations of flows over narrow (South Georgia) and broad (New Zealand) mountain barriers are used to determine the behaviour of resolved and parametrized pressure drag and gravity‐wave momentum fluxes as a function of horizontal grid length. Analysis of the pressure drag in spectral space suggests that contributions from wavelengths shorter than 8–10 grid lengths are poorly resolved and that parametrization schemes should compensate for the missing drag from processes on these scales, rather than strictly the subgrid scales. The model performance for South Georgia is such that the total (resolved plus parametrized) pressure drag is approximately invariant across a range of resolutions. The parametrized (resolved) drag increases (decreases) as the grid length increases and the resolved and parametrized drag become comparable when the characteristic island wavelength is approximately 8 times the grid length. This is not true when the same tuning of the drag parametrization is applied to New Zealand, in which case the parametrized drag increases too rapidly with increasing grid length. However, satisfactory results are obtained when the scheme is re‐tuned and it is shown that the optimal tuning for the two islands is consistent with scaling the subgrid orographic heights to be representative of the orography on longer length‐scales, of up to 10 grid lengths. The results suggest that drag schemes require orographic information on these longer scales, rather than only the subgrid scale. At the coarsest resolutions, where the island wavelength and grid length are similar, the parametrized drag is too small because the grid boxes are increasingly treated as sea points. Possible solutions to this problem are discussed.